The effect of hearing aids on postural stability. (24th October 2014) - Rumalla, Kavelin; Karim, Adham M.; Hullar, Timothy E.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis In the United States, falls are the leading cause of accidental deaths in adults aged over 65 years. Epidemiologic studies indicate that there is a correlation between hearing loss and the risk of falling among older people. The vestibular, proprioceptive, and visual systems are known to contribute to postural stability, but the contribution of audition to maintaining balance has not yet been determined. Study Design Cross‐sectional study to measure postural stability in bilateral hearing‐aid users aged over 65 years in aided and unaided conditions. Methods Balance was assessed using the Romberg on foam test and the tandem stance test. Tests were administered in the presence of a point‐source broadband white‐noise sound (0–4 kHz) source in both unaided and aided conditions in the dark. Subjective measures of balance were made using the Activities‐specific Balance Confidence Scale. Results Performance was significantly better in the aided than the unaided condition (P = 0.005 for both tests). No statistically significant relationship between improvement in balance, and hearing was identified. Participants did not report that they perceived a difference in balance between the two conditions. Conclusion These results indicate that hearing aids are a novel treatment modality for imbalance in older adults with hearing loss and suggest that wearing hearing aids may offer a significant public‐health benefit for avoiding falls in this population. Level of Evidence 4. Laryngoscope, 125:720–723, 2015